The Importance of Innovative Work Behavior in Era Industrial Revolution 4.0 - Halawa, Forman; Sridadi, Ahmad Rizki; Hardiana, Yulinda; Sundari, Anggie; Zain, Ine Alexsandrina Susiva; Ramadhan, Muhammad Naufal (Universitas Proklamasi 45, 2023)
Innovative Work Behavior (IWB) is a concept in Industrial Revolution 4.0 to encourage business growth, competitiveness, and success. Organizations that prioritize innovation and encourage creativity are expected to thrive in the current dynamic and unpredictable business environment. This study aims to provide ideas, suggestions and contributions to researchers who examine IWB variables, making it easier for researchers to determine the antecedent and consequent variables as well as the sectors to be studied. This study uses a literature review method to investigate the antecedents, consequences, and sectors that are involved in IWB by reviewing 44 articles from the Scopus database that have been reviewed. In addition, this study uses a bibliometric technique in order to find IWB’s compatibility. Results indicate that IWB has 63 antecedents and can be classified into three factors: individual, organizational, and leadership. As for consequences, it shows 6 consequences which also consist of digital literacy and competitive advantages apart from performance. Sectors that engage in IWB are predominantly telecommunication and manufacturing. It is hoped that IWB could expand to all sectors especially public sectors such as public services.